Legal Protections for Gig Workers: A Comparative Socio-legal Study of Indonesia and India - Shekhawat, Vidisha; Khare, Pranjal (UI Scholars Hub, 2025)
The platform economy has transformed the lines of labour in the last few years across both developed and developing countries. In the case of other countries, such as Indonesia and India, where informal employment has been a long-standing characteristic of the labour force, the rise of digital platforms, including Gojek, Grab, Swiggy, and Zomato, has added another layer of complexity to already existing labour issues. These services provide flexibility and earning potential, albeit in exchange for social safety nets and work rights. This paper undertakes a doctrinal and comparative socio-legal study to observe the way the legal jurisdictions of Indonesia and India are adapting to the emergence of platform-based gig work. Grounded on legal pluralism and access to justice approaches, the present research analyses the sufficiency of the existing labour laws regarding the changing characteristics of digital labour. Such statutory instruments, such as the Indonesia Omnibus Law on Job Creation or the India Code on Social Security, 2020, are used in the analysis to compare the way platform labour and its entitlements are conceptualised in different jurisdictions. Instead of conducting empirical data collection in the field, the study centres on legal sources, policy documents, and judicial opinions with the aim of finding out the normative premises behind whether the regulation of platforms is done. The research concludes that both states are prolific legislators with the tendency to implement economic liberalisation rather than labour rights, although rarely taking into consideration the vulnerability of the gig workers in the legal rhetoric. Through a socio-legal perspective, this paper indicates the contradictions between technological advancement, the dignity of workers, and legal responsibility. It demands the reconsideration of binary employment regimes and proposes implementing hybrid regulatory regimes that will consider the special status of platform workers. Finally, the article adds to the discourse of labour justice in the digital world a global south perspective that asks all policymakers to design legislation that is not total in its market-driven orientation but in social justice and equality of access to the law.